Predictive Factors of Unemployment and Real Gross National Product per Capita in EU-27: Level of Education, Performance in Program for International Student Assessment (PISA), Parents’ education, Youth migration and Financial Crisis - Christos C. FRANGOS1; Konstantinos C. FRAGKOS2; Panagiotis PLAKUDAKIS3; Abuzar Yousef Ali AHMED4 (Communications of International Proceedings, 2020)
In this paper we investigate the association between the level of education and the quality of learning outcomes which are achieved by students and the Unemployment rate expressed by the Real Gross Domestic Product per capita, in  the European Union (EU), during the years 2003 to 2018. Using the Report of the Organization of Economic Cooperation and Development (OECD), 2010: The High Cost of Low Educational Performance, we present Educational Performance and Schooling as the key drivers for increasing the Real Gross Domestic Product per capita, because the result is the rise in the supply of well-paid skilled workers who form the backbone personnel and innovative force of many enterprises. We derive two Linear Statistical Models with independent variables the level of education of the population and the educational performance of students and dependent variable the Real Gross Domestic Product per capita, for the countries of European Union. The employment opportunities of young people with special educational needs are emphasized and the efficiency of the educational systems across the Member-States of EU is examined in the light of the Report of the Program for International Student Assessment (PISA), Organization of Economic Cooperation and Development, 2018. Finally, a set of policies is suggested to the Educational Planners of European Countries for the maintenance of Economic growth using Educational tools, school reforms and increasing the ratio of teacher-student.
Keywords: Real Gross National Product per capita; special education; European Union; Program for International Student Assessment.